Karakteristik Vinegar Nanas Pada Variasi Kombinasi Kecepatan Agitasi Dan Lama Fermentasi Pada Asam Asetat - Saragih, Davina Patricia; Antara, Nyoman Semadi; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Pineapple (Ananas comosus (L.) Merr) is a tropical fruit abundant in Indonesia and rich in simple sugars such as glucose, fructose, and sucrose, making it a potential raw material for vinegar production through fermentation processes. Vinegar production involves two stages of fermentation: alcoholic fermentation using Saccharomyces cerevisiae and acetic fermentation by Acetobacter aceti. This study aims to determine the effect of agitation speed and fermentation duration during the acetic fermentation stage on the characteristics of pineapple vinegar and to identify the optimal agitation speed and fermentation duration for producing pineapple vinegar with the best characteristics. The research was conducted using a randomized block design (RBD) with two factors: agitation speed (50, 100, and 150 rpm) and fermentation duration (5, 10, and 15 days), with two replications, resulting in 18 experimental units. Data were analyzed using analysis of variance (ANOVA), followed by Duncan's multiple range test if significant effects were found. Observed parameters included acetic acid content, ethanol content, reducing sugar content, and sensory characteristics such as color, aroma, taste (sweet, sour, bitter), and overall acceptance. The results showed that agitation speed and fermentation duration significantly affected the characteristics of pineapple vinegar during the acetic fermentation stage. The best treatment was obtained at an agitation speed of 150 rpm for 10 days, yielding an acetic acid content of 3.2%, ethanol content of 0.024%, reducing sugar content of 0.201%, color score of 3.2 (slightly yellow), sweetness score of 3.6 (moderately sweet), sourness score of 3.9 (very sour), bitterness score of 3.6 (moderately bitter), and the highest overall acceptance score of 3.5 (neutral to like).